Functional independence of the elderly in multiprofessional home care (Acta Scientiarum. Health Sciences, 2019)
Functional evaluation is one of the pillars of elderly home care for planning of interventions targeting the autonomy of this population. To verify Functional Independence Measure (FIM) in senior patients on a home care program. Retrospective quantitative study with elderly patients assisted by a home care service in the city of Curitiba, from August 2012 to December 2016. The following information was collected: gender, age, clinical diagnosis, and mean FIM scores at admission and discharge. Inclusion and exclusion criteria were met, descriptive statistics was used and, for association of variables, Wilcoxon’s and Spearman’s tests were applied. 1,614 patients were included, with predominance of women (n = 953; 59.53%), mean age of 78.7 ± 9.2 years, clinical diagnoses of diseases mostly affecting the central nervous system (CNS), the respiratory system, the joint and musculoskeletal system, and the circulatory system. The initial mean FIM was 50.56 points, while the final one was 55.36 points, with significant difference – Z = -5.09, p = 0.0001. Most seniors presented maximum to moderate dependence; however, a significant improvement in FIM after the health care provided in their homes was observed in patients with minimum dependence or modified independence.